Influence of Sediment Cycling on the Rare-Earth Element Geochemistry of Fluvial Deposits (Caculuvar–Mucope, Cunene River Basin, Angola) - Armanda Cruz; Pedro A. Dinis; Alberto Gomes; Paula Leite (Geosciences, 2021)
The rare-earth element (REE) geochemistry of sedimentary deposits has been used in provenance investigations despite the transformation that this group of elements may suffer during a depositional cycle. In the present investigation, we used the geochemistry and XRD mineralogy of a set of sand and mud fluvial deposits to evaluate the ability of REE parameters in provenance tracing, and the changes in REE geochemistry associated with weathering and sorting. The analyzed deposits were generated in a subtropical drainage basin where mafic and felsic units are evenly represented, and these crystalline rocks are covered by sedimentary successions in a wide portion of the basin. A few element ratios appear to hold robust information about primary sources (Eu/Y, Eu/Eu*, LaN/YbN, LaN/SmN, and GdN/YbN), and the provenance signal is best preserved in sand than in mud deposits. Sediment cycles, however, change the REE geochemistry, affecting mud and sand deposits differently. They are responsible for significant REE depletion through quartz dilution in sands and may promote discernible changes in REE patterns in muds (e.g., increase in Ce content and some light REE depletion relative to heavy REE).